Mitochondrial Dynamics: A Potential Therapeutic Target for Ischemic Stroke - Zhou, Xiangyue; Chen, Hanmin; Wang, Ling; Lenahan, Cameron; Lian, Lifei; Ou, Yibo; He, Yue (Frontiers in Aging Neuroscience, 2021)
Stroke is one of the leading causes of death and disability worldwide. Brain injury after ischaemic stroke involves multiple pathophysiological mechanisms, such as oxidative stress, mitochondrial dysfunction, excitotoxicity, calcium overload, neuroinflammation, neuronal apoptosis, and blood-brain barrier (BBB) disruption. All of these factors are associated with dysfunctional energy metabolism after stroke. Mitochondria are organelles that provide adenosine triphosphate (ATP) to the cell through oxidative phosphorylation. Mitochondrial dynamics mean that the mitochondria are constantly changing dynamically, and maintain the normal physiological functions of the cell through continuous division and fusion. Mitochondrial dynamics are closely associated with various pathophysiological mechanisms of post stroke brain injury. In this review, we will discuss the role of the molecular mechanisms of mitochondrial dynamics in energy metabolism after ischaemic stroke and new strategies for restoring energy homeostasis and neural function. Through this, we hope to uncover new therapeutic targets for the treatment of ischaemic stroke.